Mathematical modelling of salt water intrusion in a Northern Portuguese estuary - Pinho, José L. S. (2007)
Salinity intrusion is a key issue for estuarine water quality management. Aquatic ecosystem sustainability is highly dependent on salinity concentration dynamics and must be studied for each particular environment. Salinity intrusion into the estuary of the river Lima, in the north-western region of the Iberian Peninsula, was studied based on a two-dimensional hydrodynamic and mass transport model. Tide heights and river discharges are the major causes affecting salinity intrusion, and have been analyzed by means of estuarine circulation simulation for different scenarios. The upstream propagation of the salinity front under unfavorable conditions reaches a river section located at about 12 km upstream the river mouth. The developed model constitutes a powerful tool for evaluation of the salinity intrusion pattern in the river Lima estuary, and an auxiliary instrument for decision making in river basin water management.